Spatial and Temporal Changes and Driving Factors of Soil Erosion in North Piedmont of Yinshan Mountain - Wu Shuai; Aruhan; Pan Haiwei (Shuitu baochi tongbao)
[Objective] The spatial and temporal changes of soil erosion and its influencing factors in the north piedmont of Yinshan Mountain from 2000 to 2020 were analyzed in order to provide scientific guidance for soil erosion control and land space planning in this area. [Methods] Based on precipitation, land use, soil and remote sensing image data, the research was carried out by using GIS technology and the RUSLE model. [Results] ① From 2000 to 2020, soil erosion intensity in the north piedmont of Yinshan Mountain was mainly micro-grade erosion and moderate-grade erosion. The area of high-grade erosion continued to increase over time. The soil erosion status in the north piedmont of Yinshan Mountain was very severe. ② The areas of severe soil erosion in the north piedmont of Yinshan Mountain were mainly located along the Yinshan Mountain range and most areas of Duolun County, Inner Mongolia Autonomous Region. ③ Land use type was the main influencing factor of soil erosion in the north piedmont of Yinshan Mountain. The explanatory power of each factor followed the order of: land use type > vegetation coverage > rainfall > slope. The area consisting of cultivated land with vegetation coverage less than 0.3, slope of 15°~20°, and rainfall of 365~413 mm was the high risk erosion area. [Conclusion] The degree of soil erosion in the north piedmont of Yinshan Mountain was generally high. Cultivated land and grassland with low vegetation coverage should be the key areas for soil erosion control in the north piedmont of Yinshan Mountain. Soil erosion should be controlled by planting trees and grasses to expand the coverage of forests and grasslands, improve vegetation coverage, reduce surface runoff rate, and improve infiltration capacity.